SISTEM KOMUNIKASI TERPADU DAN PENERAPANNYA PADA KINERJA MANAJEMEN PUNCAK - Firmansyah, - (Jurnal Ilmiah Widya, 2013)
All the information in the integrated communications system is input in the Executive information system that can be used to plan strategy Executive. The purpose of this paper is to: (1) provide information and the development of information and communication technologies that can provide convenience and benefits for the company and the wearer 2. Discuss the effectiveness of the integrated communications system on the performance of top management. The method used is the library research with a descriptive, exploratory analysis approach. It can be concluded that: (1) Office Automation (OA) provide a significant change to the company especially for the managers of the Summit to improve its performance by utilizing a good source of information related to the work of the Government, as well as in companies, (2) the Foundation of making management strategy is to build the management of Integrated communication system that includes data on all (3) the benefits of the integrated Control System which reduces the cost of facilities, equipment costs all the more give attention on communication networks, reducing the work ceased, and social contributions.